Community structure of polypores (Basidiomycota) in a restored Brazilian Forest - Alcantara, Alex Almeida; Matheus Pires, Ricardo; Pereira Cabral Gomes, Eduardo; Barbosa, Luiz Mauro; Mello Gugliotta, Adriana (Lilloa, 2022)
Polypores (Basidiomycota) are of great importance in several forest areas since they are fundamental for wood decomposition and nutrient recycling, which is essential for the functioning of ecosystems. This study assessed the polypore community structure in a restoration area and its use as a parameter to monitor restoration. Our study was carried out in Parque Florestal São Marcelo Private Natural Heritage Reserve (RPPN), a protected area of 240 ha, formed in 2002 from reforestation with native species, 13 years after the restoration measures. The polypore community in the area was characterized according to the richness, abundance, and functionality. Results were compared with data from two natural reference areas near the study site and in the same forest type, i.e., riparian forest, but with different land use history. One hundred and eighteen specimens belonging to 31 species were collected; 6.45% were abundant (Funalia rigida and Pycnoporus sanguineus), 12.90% common, 32.26% occasional, and 48.39% rare. Four functional groups based on the species' relative frequency on each substrate were found. Higher frequency of polypores was observed in substrates of smaller diameter (dead branches). The restored area showed a similar richness to the preserved area used as reference. In addition, the polypore community showed a structure similar to well-established areas. This result indicates that the RPPN restoration project was successful and that the polypore community structure can be suitable for evaluating and monitoring regions restored over time.